Variasi Bowing Etudes Ou Caprices No. 2 Rodolphe Kreutzer Sebagai Strategi Pembentukan Teknik Tangan Kanan Pada Pemain Violin - Sagaf Adzkia; Alya Sabina Muntasya (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
Violin players are required to have balanced technical skills not only with the left hand (finger operation on the strings), but also the role of the right hand (playing the bow). Qualifications that emphasize exercises that focus on right-hand skills are in fact often under-appreciated. This research proposal presents a study-based violin learning strategy that emphasizes right hand skills through bowing variation treatment, which is applied to Rodolphe Kreutzer's Etudes Ou Caprices No. 2. The focus of this research is the music education study program, ISI Yogyakarta. This study uses a qualitative method with a musicological approach. The stages that were passed in this research were through the process of literature study, observation, interviews, and analysis. The results of this study are: the emergence of eight variations of bowing which was applied to Etudes Ou Caprices no.2 Rodolphe Kreutzer; the treatment applied is useful in improving the right hand technique and the differentiating specifications between each bowing technique; through continuous practice of bowing variation techniques can make students responsive in reading notation symbols, especially on the diversity of right-handed techniques; treatment of variations of bowing detache, staccato, spiccato, legato, and their variations can be easily applied to the repertoire/songs being studied to support interpretation.